The Effectiveness of Using the Cake App to Improve Students’ Speaking Ability: Efektivitas Penggunaan Aplikasi Cake dalam Meningkatkan Kemampuan Berbicara Siswa - Naba Khilma; Siti Nurul Azkiyah (Bestari: Jurnal Pendidikan dan Kebudayaan, 2026)
This study aims to determine the effectiveness of the Cake application in improving the speaking ability of first-grade students at SMAN 11 Tangerang Selatan in the 2025/2026 academic year. A quasi-experimental design with experimental and control groups was employed using pre-test and post-test. Data were analyzed using paired sample t-test, ANCOVA, and N-Gain through SPSS 25. The results reveal that the experimental group achieved a higher post-test mean score (72.48) than the control group (70.55) with a medium N-Gain score (45.81). Statistical findings confirmed a significant effect of the Cake application on students’ speaking ability after controlling the pre-test scores (p < 0.05). Therefore, the Cake application is effective in enhancing students’ speaking ability, particularly in pronunciation, fluency, and vocabulary.